2022
DOI: 10.3389/fphar.2022.971113
|View full text |Cite
|
Sign up to set email alerts
|

Research and application of herbal medicine in the treatment of chronic kidney disease since the 21st century: A visualized bibliometric analysis

Abstract: Background: Here, a bibliometric and knowledge-map analysis was used to analyze the research status and application of herbal medicine for the treatment of chronic kidney disease (CKD). By looking for research hotspots and key topics, we provide new clues and research directions for future research.Methods: Articles and reviews regarding herbal medicine in the treatment of CKD were retrieved from the Web of Science Core Collection on 23 May 2022. The R-bibliometrix, VOSviewer, and CiteSpace software were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Bibliometric analysis is an effective and feasible method for understanding research trends and focal areas within a given field, ultimately aiding researchers and clinicians in shaping future investigations and clinical treatments. [35,36] This bibliometric analysis investigated the relationship between the gut microbiota and CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometric analysis is an effective and feasible method for understanding research trends and focal areas within a given field, ultimately aiding researchers and clinicians in shaping future investigations and clinical treatments. [35,36] This bibliometric analysis investigated the relationship between the gut microbiota and CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In traditional medicine in the East and West, herbal prescriptions that are composed of several medicinal plants have been used to alleviate fibrotic diseases of the major organs, including the liver, kidneys, and lungs [11][12][13]. Interestingly, plant extracts with these effects contain several polyphenolic compounds in common, and studies on the pharmacological effects of these compounds are attracting attention [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…7 In recent years, herbal therapies have been recognized as a dietary supplement for the treatment of various diseases, including cancer, diabetes, and CKD. [8][9][10][11] In clinical investigations, it has been demonstrated that numerous of herbal remedies have renoprotective effects and improve the outcomes of diseases by activating antioxidant defense mechanisms and reducing proinflammatory signaling pathways. [12][13] For instance, previous study found that curcumin therapy for three months reduced the levels of inflammation-related markers in CKD patients receiving hemodialysis.…”
Section: Introductionmentioning
confidence: 99%